Fitting In or Standing Out? The Tradeoffs of Structural and Cultural Embeddedness. (December 2016) - Goldberg, Amir; Srivastava, Sameer B.; Manian, V. Govind; Monroe, William; Potts, Christopher
A recurring theme in sociological research is the tradeoff between fitting in and standing out. Prior work examining this tension tends to take either a structural or a cultural perspective. We fuse these two traditions to develop a theory of how structural and cultural embeddedness jointly relate to individual attainment within organizations. Given that organizational culture is hard to observe, we develop a novel approach to assessing individuals' cultural fit with their colleagues based on the language expressed in internal e-mail communications. Drawing on a unique dataset that includes a corpus of 10.24 million e-mail messages exchanged over five years among 601 employees in a high-technology firm, we find that network constraint impedes, whereas cultural fit promotes, individual attainment. More importantly, we find evidence of a tradeoff between the two forms of embeddedness: cultural fit benefits individuals with low network constraint (i.e., brokers), whereas network constraint promotes attainment for people with low cultural fit.